The Precise Molecular Location of Gadolinium Atoms has a Significant Influence on the Efficacy of Nanoparticulate MRI Positive Contrast Agents - Li, Y.; Laurent, S.; Esser, L.; Vander Elst, L.; Muller, R.; Lowe, Andrew; Boyer, C.; Davis, T. (R S C Publications, 2014)
In this work, we studied the influence of the structure of macromolecular ligands on the relaxivity of gadolinium contrast agents constructed as nanoparticle systems. Macromolecular ligands were assembled as single-molecule nanoparticles in the form of either discrete core cross-linked star polymers or hyperbranched polymers. 1-(5-Amino-3-aza-2-oxypentyl)-4,7,10-tris(tert-butoxycarbonylmethyl)-1,4,7,10-tetraaza-cyclododecane (DO3A–tBu–NH2) chelate was incorporated into different parts (arms, cores, and end-groups) of the polymeric structures using activated ester/amine nucleophilic substitutions, deprotected and complexed with Gd3+. The relaxivity properties of the ligated Gd3+ agents were then studied to evaluate the effect of macromolecular architecture and Gd3+ placement on their behavior as discrete nanoparticle magnetic resonance imaging (MRI) contrast agents. The precise placement of Gd3+ in the polymeric structures (and therefore in the nanoparticles) proved to be critical in optimizing the performance of the nanoparticles as MRI contrast agents. The relaxivity was measured to vary from 11 to 22 mM−1 s−1, 2–5 times higher than that of a commercial DOTA–Gd contrast agent when using a magnetic field strength of 0.47 T. The relaxivity of these nanoparticles was examined at different magnetic fields from 0.47 T to 9.4 T. Finally, the residence time of the coordinated water (τM) and the rotational correlation time of the final molecule (τR) were evaluated for these different nanostructures and correlated with the polymeric architecture.